Efisiensi Pupuk Urea Dan Lahan Dalam Meningkatkan Hasil Jagung â€œDouble Rowâ€ Pada Pola Tanam Tumpang Sari Dengan Kacang Tanah - Andrestu Kesuma; Niar Nurmauli; Paul B. Timotiwu; Herawati Hamim (Jurnal Penelitian Pertanian Terapan, 2018)
Mixed cropping of corn and peanut in â€œdouble rowâ€ is expected increase efficiency of ureafertilizing and efficiency of land utilization. This research aimed to evaluate the efficiency ofthe urea fertilizing on corn production and to evaluate the efficiency of land utilization inâ€œdouble rowâ€ mixed with peanut. The research conducted in Field of Laboratory LapangTerpadu and Laboratory Ilmu Tanam Faculty of Agriculture University of Lampung fromJuly to October 2014. The experiment used Complete block design with nine treatments andthree replications. The results showed that intercropping of corn â€œdouble rowâ€ and peanutsdid not affect the efficiency of urea. However, the cropping system increased land utilization.The value of land use efficiency based on yield per hectare has the highest yield at a dose of300 kg urea/ ha that is equal to 1,76. While giving urea fertilizer at dose 0, 50, 100, 150,200, and 250 kg/ ha shows the efficiency of land use amounted to 1,18; 1,20; 1,31; 1,53;1,66; and 1,44.